Direct identification of HLA‐presented CD8 T cell epitopes from transmitted founder HIV‐1 variants. Issue 17 (1st August 2021) - Hare, Jonathan; Macharia, Gladys; Yue, Ling; Streatfield, Claire L.; Hunter, Eric; Purcell, Anthony; Ternette, Nicola; Gilmour, Jill
Abstract: Cytotoxic T lymphocytes (CTLs) are a critical arm of the immune response to viral infections. The activation and expansion of antigen specific CTL requires recognition of peptide antigens presented on class I major histocompatibility complex molecules (MHC‐1) of infected cells. Methods to identify presented peptide antigens that do not rely on the pre‐existence of antigen specific CTL are critical to the development of new vaccines. We infected activated CD4+ T cells with two HIV‐1 transmitted founder (TF) isolates and used high‐resolution mass spectrometry (MS) to identify HIV peptides bound on MHC‐1. Using this approach, we identified 14 MHC‐1 bound peptides from across the two TF isolates. Assessment of predicted binding thresholds revealed good association of the identified peptides to the shared HLA alleles between the HIV+ donors and the naïve PBMC sample with three peptides identified through peptide sequencing inducing a CD8 T‐cell response ( p < 0.05). Direct infection of naïve CD4 cells by HIV TF isolates and sequencing of MHC‐I presented peptides by HPLC‐MS/MS enables identification of novel peptides that may be missed by alternative epitope mapping strategies and can provide valuable insight in to the first peptides presented by an HIV‐infected CD4 cell in the first few days post infection.